Emergence of Attenuated Measles Illness Among IgG-positive/IgM-negative Measles Cases: Victoria, Australia, 2008–2017. (16th May 2019) - Gibney, Katherine B; Attwood, Lucy O; Nicholson, Suellen; Tran, Thomas; Druce, Julian; Healy, Julia; Strachan, Janet; Franklin, Lucinda; Hall, Robert; Cross, Gail B
Abstract: Background: Waning measles immunity among vaccinated individuals may result in an attenuated illness. This study compares the epidemiological, clinical, and laboratory profile of measles cases with waning immunity with other measles cases. Methods: Polymerase chain reaction–positive (+) measles cases notified to Victoria's Department of Health and Human Services from 2008 to 2017 with immunoglobulin (Ig) M and IgG tested at diagnosis were classified according to serology at diagnosis: IgG negative (−) (nonimmune), IgM+/IgG+ (indeterminate), or IgM−/IgG+ (waning immunity). Results: Between 2008 and 2017, 297 measles cases were notified, of whom 190 (64%) were included; 151 of 190 (79%) were nonimmune at diagnosis, 26 (14%) were indeterminate, and 13 (7%) had waning immunity. Between 2008–2013 and 2014–2017, the proportion of cases with waning immunity increased from 0 of 87 (0%) to 13 of 103 (13%) ( P < .001) and the diagnostic sensitivity of initial IgM fell from 93% to 81% ( P = .012), respectively. Seven (54%) waning immunity cases reported receiving measles-containing vaccines; 1 case had 2 documented doses. Compared with nonimmune and indeterminate cases, waning immunity cases were more likely to be male; less likely to report fever, coryza, and cough; and had lower burden of virus (higher cycle threshold values). Waning immunity cases had higher IgG titers than indeterminate cases (mean optical density values, 1.96 vs 0.71; P = .004). Onward transmission from 1 waning immunity case was documented. Conclusions: Waning immunity among measles cases, associated with secondary vaccine failure and modified clinical illness, is emerging in Victoria with transmission potential. Abstract : Between 2008 and 2018 an increase in IgM−/IgG+ measles cases was observed in Victoria, Australia. The 13 cases identified were commonly vaccinated men with attenuated illnesses, low viral loads, and high IgG titers. Onward transmission was documented from 1 case.